2007
DOI: 10.1128/aem.02350-06
|View full text |Cite
|
Sign up to set email alerts
|

Production of Dehydroamino Acid-Containing Peptides by Lactococcus lactis

Abstract: Nisin is a pentacyclic peptide antibiotic produced by some Lactococcus lactis strains. Nisin contains dehydroresidues and thioether rings that are posttranslationally introduced by a membrane-associated enzyme complex, composed of a serine and threonine dehydratase NisB and the cyclase NisC. In addition, the transporter NisT is necessary for export of the modified peptide. We studied the potential of L. lactis expressing NisB and NisT to produce peptides whose serines and threonines are dehydrated. L. lactis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 30 publications
6
84
0
4
Order By: Relevance
“…The absence of any inhibitory activity of these products also demonstrates that the truncated leader peptide keeps mutacin 1140 in an inactive structural state. It has been shown that the biosynthesis of nisin in the absence of LanP produces partially cleaved leader peptide products (41,42), with the full-length leader peptide being the main product (43). Unlike nisin, only a single truncated leader peptide product is observed for the mutacin 1140 leader peptide.…”
Section: Lanp Cleavage Sitementioning
confidence: 99%
“…The absence of any inhibitory activity of these products also demonstrates that the truncated leader peptide keeps mutacin 1140 in an inactive structural state. It has been shown that the biosynthesis of nisin in the absence of LanP produces partially cleaved leader peptide products (41,42), with the full-length leader peptide being the main product (43). Unlike nisin, only a single truncated leader peptide product is observed for the mutacin 1140 leader peptide.…”
Section: Lanp Cleavage Sitementioning
confidence: 99%
“…There have been over 80 different directed mutations reported on the nisin core peptide (23,24). In addition, a large bank of randomly mutated nisin derivatives was screened, which resulted in the identification of three mutants that significantly improved the bioactivity of nisin (23).…”
mentioning
confidence: 99%
“…It may act in a protective role for the producing organism, as its removal is required for bioactivity (10)(11)(12)(13)(14)(15). The leader peptide could also serve as a recognition motif for the transport machinery because non-lantibiotic peptides attached to leader peptides are secreted (16,17), or as a scaffold for the lantibiotic synthetases (11,(18)(19)(20). Recently, it was shown that the leader sequence of LctA, while important for processing by LctM, is not absolutely required for activity (21).…”
mentioning
confidence: 99%